A numerical study for heat and fluid flow of couple stress fluid over a spiraling disk by Legendre wavelet spectral collocation method. Issue 8 (5th June 2020) - Sadiq, M. N.; Sajid, M.; Javed, T.; Ali, N.
Abstract: This article aims to explore the spiraling motion of a couple stress fluid over a disk rotating and radially stretching simultaneously. The spiraling motion is developed through the uniform rotation of the disk in addition to radial stretching. The logarithmic spirals in the disk velocity are produced due to the combined effects of stretching and rotation. The similarity transformations are invoked to obtain the coupled ordinary differential equations representing the flow. A Legendre wavelet spectral collocation method (LWSM) is employed for obtaining numerical solutions to analyze the effects of the pertinent parameters on the flow. The quantities of physical interest, i.e., radial and azimuthal skin friction coefficients, the wall shear stress, and the heat transfer rate are computed for the various values of the spiral angle, spiraling parameter, and couple stress parameter. It is found that enhancing the spiral angle declines the radial skin friction while enhancing azimuthal skin friction and the total wall shear stress. The temperature of the fluid is decreased for increasing the spiraling parameter and spiral angle, but increases for large couple stress parameter. Abstract : This article aims to explore the spiraling motion of a couple stress fluid over a disk rotating and radially stretching simultaneously. The spiraling motion is developed through the uniform rotation of the disk in addition to radial stretching. The logarithmic spirals in the disk velocity are produced due to the combined effects of stretching and rotation. The similarity transformations are invoked to obtain the coupled ordinary differential equations representing the flow….